Upaya Meningkatkan Kesadaran Dalam Melestarikan Sumber Daya Alam Melalui Media Sosial Bagi Generasi Muda Ciliwung - Wijayanti, Vera; Sary, Marisa Puspita; Putri, Angieta Dewati; Wulandari, Helyana; Fauziyah, Hasna Nur (Edumedia Solution, 2023)
The declining concern of the younger generation towards conserving natural resources. Natural resources are natural resources that are utilized by humans to meet the needs of life, not only humans but every living creature needs natural resources to fulfill their lives. The achievement targets in this community service activity are: (1) Increasing awareness in preserving natural resources in the younger generation, (2) Increasing the motivation of the younger generation in preserving natural resources, and (3) Expanding natural resources that are maximally utilized by the younger generation. The place of this community service activity was carried out at the pavilion owned by the Mat Peci Ciliwung Community. The training ctivities were attended by members of the Mat Peci Ciliwung Community